PENGARUH EKSPOR, INVESTASI, DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP PRODUK DOMESTIK BRUTO (PDB) DI INDONESIA - Naila, Putri; Abbas, Tarmizi; Abubakar, Jariah (Jurnal Ekonomi Regional Unimal, 2023)
This research aims to determine the influence of Exports, Investment and the Human Development Index (HDI) on Gross Domestic Product (GDP) in Indonesia in 1993 - 2022. This research uses secondary data in the form of a time series for 30 years. This research uses the Autoregressive Distributed Lag (ARDL) test analysis method. The results of this research show that in the short term the export variable has a positive and significant effect, and in the long term exports has a positive and insignificant effect on GDP in Indonesia. In the short term, investment variables have a positive and significant effect, as well as in the long term, investment has a positive and significant effect on GDP in Indonesia. In the short term HDI has a negative and significant effect, and in the long term HDI has a negative and insignificant effect on GDP in Indonesia. It is hoped that the Government can increase GDP by improving people's welfare, so that it can have an impact on people's ability to carry out production which can ultimately be exported to other countries.